PENGARUH PEMBERIAN ASI EKSKLUSIF TERHADAP PERKEMBANGAN BAYI USIA 6-12 BULAN DI DESA CANDIMULYO KEC. JOMBANG KAB. JOMBANG - Shofiyah, Siti (LPPM STIKes Bahrul Ulum Jombang, 2019)
Infancy is a vital period in which physical and mental state of the baby becomes the foundation for baby development. This period must be optimized by keeping the baby’s health and its nutritional status by giving exclusive breastfeeding. This research was conducted by using an analytical design with a cross-sectional approach. The population of the research was 96 infants aged 6, 9, 12 as respondents and 77 respondents as a sample taken by using simple random sampling and statistical testing of Spearman’s rho. The research instrument was a questionnaire and KPSP. The data were analyzed by using some steps, they are editing, coding scoring, and tabulating. The result showed that respondents who are exclusively breastfed are 31 ( 40.3 % ) , the majority of respondents experienced a corresponding growth of 21 ( 58.5 %), on the contrary infants that are not exclusively breastfed by 46 ( 59.7 % ) experienced growth doubted 25 ( 44.1 % ) of the total that had been developed to deviate as much as 8 ( 10.4 % ). Statistical test results of Spearman 's rho obtained ρ value ( 0.001 ) < α (0.05 ) so that H0 rejected and H1 accepted. There was an influence of exclusive breastfeeding on the development of infants aged 6-12 months in Candimulyo Jombang.